Pengaruh Penggunaan Media Sosial Instagram @indonesiainbangkok terhadap Pemenuhan Kebutuhan Informasi Followers - Gelvani Benedikta Situmorang; Bambang Sujarwadi (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Social media as one of the technological developments has brought changes to people's lives to become an information society. Social media is also used by the government, one of which is the Embassy of the Republic of Indonesia in Bangkok, which is used to share information related to foreign government policies that the public needs. To create informative dissemination, interactive communication is needed between followers and information providers. However, analysis of activity on social media accounts shows patterns that are not yet effective, so this research was carried out which aims to determine the effect of using the social media Instagram @indonesiainbangkok on meeting followers' information needs. The theory in this research is the theory of social media use by Lometti, Reeves, and Bybee which consists of the amount of time, media content, and media relationship with individuals. This research uses quantitative research methods with data collection techniques using questionnaires distributed online. The population in this study was 11,600, then a sample of 100 people was obtained. Sampling in this study used a simple random sampling method or random without certain criteria. The data analysis method in this research uses simple linear regression analysis and coefficient of determination. The research results show that the use of social media Instagram @indonesiainbangkok has quite a large influence on fulfilling followers' information needs, namely 95.3% which means that the majority of followers of the @indonesiainbangkok Instagram account fulfill their information needs. Through this research, it is hoped that both followers and managers of Instagram @indonesiainbangkok can create more interactive and two-way communication for mutual comfort.